2009
DOI: 10.1111/j.1462-5822.2009.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Galactofuranose attenuates cellular adhesion ofAspergillus fumigatus

Abstract: SummaryGalactofuranose (Galf) is a major molecule found in cell wall polysaccharides, secreted glycoproteins, membrane lipophosphoglycans and sphingolipids of Aspergillus fumigatus. The initial step in the Galf synthetic pathway is the re-arrangement of UDP-galactopyranose to UDP-Galf through the action of UDP-galactopyranose mutase. A mutant lacking the AfUGM1 gene encoding the UDPgalactopyranose mutase has been constructed. In the mutant, though there is a moderate reduction in the mycelial growth associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
115
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 45 publications
(57 reference statements)
11
115
1
Order By: Relevance
“…These data are consistent with those from mutations in other components of the galactomannan biosynthetic pathways. For example, deletion of ugm1 in A. fumigatus resulted not only in an absence of galactomannan but also an increase in galactosaminogalactan synthesis and biofilm adherence (6). Although galactosaminogalactan production has not been studied in A. nidulans, it was reported that the deletion of ugmA and ugeA was associated with an increase in adherence (55), suggesting a similar phenomenon may also occur in this organism.…”
Section: Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are consistent with those from mutations in other components of the galactomannan biosynthetic pathways. For example, deletion of ugm1 in A. fumigatus resulted not only in an absence of galactomannan but also an increase in galactosaminogalactan synthesis and biofilm adherence (6). Although galactosaminogalactan production has not been studied in A. nidulans, it was reported that the deletion of ugmA and ugeA was associated with an increase in adherence (55), suggesting a similar phenomenon may also occur in this organism.…”
Section: Speciesmentioning
confidence: 99%
“…latory controls at various levels of gene expression and protein synthesis of other pathway components. Although a deficiency in galactosaminogalactan is not lethal, it renders the strain nonadherent, which is not the case for galactomannan deficiency (5,6,8,12,22). Thus, in the absence of a specific requirement for galactomannan, it is possible that the fungus preferentially diverts its resources to preserve galactosaminogalactan synthesis for adherence to surfaces or biofilm homeostasis.…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Leishmania, loss of Galf synthesis or of the key galactofuranosyltransferase required to synthesize surface lipophosphoglycan results in severe defects in survival both in the insect and in the early stages of mammalian infection (15)(16)(17)(18). In the pathogenic fungus Aspergillus fumigatus, the presence of Galf in secreted glycoproteins, glycolipids, and cell wall polysaccharides (7,8) improves cell integrity (19 -21) and reduces adhe-sion to mammalian epithelial and endothelial surfaces by shielding underlying mannan structures (20). Galf may also play a role in immune recognition of pathogenic microbes.…”
mentioning
confidence: 99%
“…Galactomannan, which consists of a mannan core decorated with ␤-1,5-linked galactofuranose, is dispensable for biofilm formation, and galactofuranose-deficient mutants exhibit increased biofilm formation as a consequence of increased production of GAG (8,10,16). ␣-Glucans are abundant within the biofilm matrix; however, the role of this polysaccharide in biofilm formation has not been studied (13,(17)(18)(19).…”
Section: A Fumigatus Biofilm Exopolysaccharidesmentioning
confidence: 99%